Posttranslational modification at the N terminus of the human adenovirus type 12 E1A 235R tumor antigen. - Lucher, L A (1986)
The adenovirus E1A transforming region, which encodes immortalization, partial cell transformation, and gene activation functions, expresses two early mRNAs, 13S and 12S. Multiple-T antigen species with different electrophoretic mobilities are formed from each mRNA, presumably by unknown posttranslational modifications. The adenovirus type 12 (Ad12) 13S and 12S mRNAs encode E1A T antigens of 266 and 235 amino acid residues (266R and 235R), respectively. To study possible posttranslational processing at the N and C termini and to distinguish between the Ad12 266R and 235R T antigens, we prepared antibodies targeted to synthetic peptides encoded at the common C (peptide 204) and N (peptide 202) termini of the 266R and 235R T antigens and at the unique internal domain of the 266R T antigen (peptide 206). The specificity of each anti-peptide antibody was confirmed by immunoprecipitation of the 266R and 235R T antigens produced in Escherichia coli. Immunoprecipitation analysis of the E1A T antigens synthesized in Ad12-infected KB cells revealed the following. Antibody to the common C terminus recognized three T antigens with apparent Mrs of 43,000, 42,000, and 39,000 (43K, 42K, and 39K). All three forms were phosphorylated and were present in both the nucleus and the cytoplasm. The 43K and 42K T antigens were rapidly synthesized during a 10-min pulse with [35S]methionine in Ad12-infected cells. The 43K T antigen had a half-life of 20 min, the 42K T antigen had a longer half-life of about 40 min, and the 39K T antigen became the predominant E1A T antigen. Antibodies to the unique region immunoprecipitated the 43K T antigen but not the 42K and 39K T antigens. Antibody to the N terminus immunoprecipitated the 43K and 42K T antigens but not the 39K T antigen, suggesting that the 39K T antigen possessed a modified N terminus. Partial N-terminal amino acid sequence analysis showed that the 43K and 42K T antigens contain methionine at residues 1 and 5, as predicted from the DNA sequence, whereas no methionine was released from the 39K T antigen during the first six cycles of Edman degradation. We propose that the short-lived 43K T antigen is the primary product of the 13S mRNA, the 266R T antigen; the somewhat more stable 42K T antigen is the primary product of the 12S mRNA, the 235R T antigen.(ABSTRACT TRUNCATED AT 400 WORDS)